2014
DOI: 10.3892/mmr.2014.2914
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 is a promising molecular target in the diagnosis of cancer (Review)

Abstract: The expression of Ki67 is strongly associated with tumor cell proliferation and growth, and is widely used in routine pathological investigation as a proliferation marker. The nuclear protein Ki67 (pKi67) is an established prognostic and predictive indicator for the assessment of biopsies from patients with cancer. Clinically, pKi67 has been shown to correlate with metastasis and the clinical stage of tumors. In addition, it has been shown that Ki67 expression is significantly higher malignant tissues with poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
445
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(521 citation statements)
references
References 113 publications
14
445
1
13
Order By: Relevance
“…We found that the expression of several genes were influenced by HMGA1P7 including also genes involved in cancer progression such as Col6a3, Mki67, H19, Igf2, Gpx3 and Leprel1 3031323334353637. Indeed, oncomine analyses and tissue-microarray immunohistochemistry showed overexpression of COL6A3 in colorectal carcinomas that was significantly and directly correlated with Dukes stage, T stage, stage, recurrence and smoking status and then with a poor prognosis30.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We found that the expression of several genes were influenced by HMGA1P7 including also genes involved in cancer progression such as Col6a3, Mki67, H19, Igf2, Gpx3 and Leprel1 3031323334353637. Indeed, oncomine analyses and tissue-microarray immunohistochemistry showed overexpression of COL6A3 in colorectal carcinomas that was significantly and directly correlated with Dukes stage, T stage, stage, recurrence and smoking status and then with a poor prognosis30.…”
Section: Discussionmentioning
confidence: 88%
“…1, the quantitative qRT-PCR analyses confirmed the data obtained from the RNA-seq analyses. Interestingly, these genes have been related to several human cancers (colon, gastric, liver, breast and hematological cancers), and are considered possible therapeutic targets303132333435.…”
Section: Resultsmentioning
confidence: 99%
“…Among these proteins, the widely used proliferation markers Mk167 (Ki67) and Top2␣ [23,24] and the nuclear targeted mitogen Hdgf [25,26] were all induced by PFOS exposure, as determined by iTRAQ assay and confirmed by western blot assay. These data suggest that PFOS probably stimulated HL-7702 proliferation under the experimental conditions.…”
Section: Discussionmentioning
confidence: 93%
“…After 26 days of EgKI-1 treatment there was ~60% reduction of tumor growth in treated mice compared with controls. As Ki67 expression is strongly associated with tumor cell proliferation [30], the significantly decreased numbers of Ki67-positive cells in tumor tissues treated with EgKI-1 reflect its inhibitory effect on cell proliferation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 is a nuclear protein that is expressed in proliferating cells and is thus a marker for cell proliferation in solid tumors [30]. Ki67 stained slides were then scanned at 20× magnification with an Aperio Scanscope XT slidescanner and digital images were analyzed with ImageScope viewing software.…”
Section: Methodsmentioning
confidence: 99%